Pedagogical Practice: Efforts To Internalize Character Education Values Based On PPKn In High School - Pratikawati, Evy; Robandi, Babang (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
This study examines pedagogical practices in Pancasila and Citizenship Education (PPKn) learning as an effort to internalize character education values ​​in high schools. The purpose of this study is to analyze the forms of pedagogical practices, internalized character values, the process of value internalization, and supporting and inhibiting factors in PPKn learning. The method used is a literature review (library research) through a critical review of books, recent scientific journal articles, and relevant education policy documents. The results indicate that dialogic, reflective, and contextual pedagogical practices enable a more meaningful internalization of character values ​​such as responsibility, tolerance, democratic attitudes, and national awareness. The discussion emphasizes that the role of teachers, humanistic pedagogical relationships, and contextual learning design are key factors for success, despite the challenges of cognitive orientation and social dynamics. This study concludes that strengthening pedagogical practices in PPKn learning is an important foundation for transformative and sustainable character education.